Comprehensive Assessment of the Physical Development of Children 4-7 Years Old in The City of Bukhara - Samadova Kh.S. (Scholars Digest Publishing, 2023)
An essential factor determining the health status of the population is the maintenance of optimal physical activity throughout the life of every citizen.. The relationship between the level of physical development and motor activity of children aged 4-7 years with the living conditions, as well as the constitutional features of the body, is determined.
Keywords: physical development, body length, head and chest circumference, constitutional feature.